RISK FACTORS FOR OROFACIAL CONGENITAL ANOMALIES IN NEONATES - Adhie Nur Radityo; Muhammad Sholeh Kosim; Kamilah Budhi; Gatot Irawan Santosa; Arsirta Eka Rini (Faculty of Medicine Diponegoro University, 2016)
ABSTRACTBackground. Orofacialanomalies are anatomical and physiological abnormalities in the structure of organs in the face which are present since birth. Previous studies found that 40-60% the cause of birth defects was unclear.Objective. To determine the risk factors for orofacial congenital anomalies in neonates.Methods. Retrospective observational study using case-control design based on medical records within January 2009-June 2013 in Kariadi Hospital was done. Subjects were selected by purposive sampling and simple randomize sampling. Risk factors studied were risky maternal age, intrauterine infection, lack of folic acid supplementation, low antenatal care and family history of orofacial anomalies. Statistical analysis were using Chi-square test, Mann-Whitney test, Kolmogorov-Smirnov test and unpaired t-test.Results. Subjects were 48 neonates, which 24 of them with orofacial anomalies. We found that significant factors of orofacialanomalies occurrence are risky maternal age (p = 0.000; OR = 11.667, 95% CI = 2.696-50.490), intrauterine infection (p = 0.000; OR = 15.400, 95% CI = 2.930-80.951), lack of folic acid supplementation (p = 0.003; OR = 7.000, 95% CI = 1.822-26.887) and low antenatal care (p = 0.000; OR = 38.333, 95% CI = 4.395-334.382) and they become not significant after had multivariate analysis.Conclusion. Maternal age, intrauterine infection, lack of folic acid supplementation and low antenatal care are risk factors for orofacial anomalies in neonates Keywords:orofacialanomalies, risk factor